UPAYA PENINGKATAN KESADARAN HUKUM MASYARAKAT PEMOHON SURAT IJIN MENGEMUDI DI SATLANTAS POLRESTA MAGELANG - Mustofa, Ishom; Mathori, Muhammad (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This research aims to describe the reasons why the increase in legal awareness among people applying for driving licenses at the Magelang Police Traffic Unit is still not optimal and to formulate efforts to increase legal awareness among the people applying for driving licenses at the Magelang Police Traffic Unit.The research design used is descriptive quantitative research supported by data obtained by observation, interviews and involvement with the research object. The sample for this study was 100 SIM applicants. Data analysis uses a qualitative analysis model using the average method and the Miles & Hubberman model.The results of the research show that the cause of increasing legal awareness among people applying for driving licenses at the Magelang Police Traffic Unit is still not optimal, namely due to lack of socialization, lack of knowledge regarding the contents of traffic regulations, there are still people who have a less obedient or obedient attitude towards the regulations, There are still emerging patterns of legal behavior that hope for ease in making a SIM with an Online SIM, Mobile SIM and also socialization. Efforts to increase legal awareness among people who apply for driving licenses at the Magelang Police Traffic Unit in this research are increasing the knowledge of Satlantas Members with various activities such as coaching at morning assembly, and new training and then conducting socialization to the community to increase knowledge about driving license regulations, Magelang Police Traffic Unit Members carry out socialization and education to the public so that they want to read and learn about the contents of the regulations by reading the Knowledge about Driving License (SIM) module which is widely available on the internet, organizing traffic counseling and education in schools, carrying out Enforcement, Order and Discipline Operations (Ops Gaktibplin) ) then the legal attitude for the community in making a SIM C, is developed by increasing understanding of the regulations for making a SIM. You can learn by accessing the material by looking at the site www.korlantas.polri.go.id. Patterns of legal behavior in making SIM C by providing convenience in making SIMs with Online SIMs, Mobile SIMs, service innovation and also socialization via radio, and the POLRI Super App.